Melatonin alleviates renal injury by activating mitophagy in diabetic nephropathy - Tang, Hanfen; Yang, Ming; Liu, Yinghong; Zhu, Xuejing; Liu, Shiping; Liu, Hong; Sun, Lin; Song, Panai (Frontiers in Endocrinology, 2022)
Diabetic nephropathy (DN) has serious renal tubule and interstitial damage, but effective prevention and treatment measures are lacking. Abnormal mitophagy may be involved in the progression of DN, but its upstream and downstream regulatory mechanism remains unclear. Melatonin, a pineal hormone associated with circadian rhythms, is involved in regulating mitochondrial homeostasis. Here, we demonstrated abnormal mitophagy in the kidney of DN mice or HG-treated HK-2 cells, which was accompanied by the raised oxidative stress and inflammation. At the same time, the treatment of melatonin could alleviate kidney damage. After mitochondrial isolation, we found that melatonin promoted AMPK phosphorylation and accelerated the translocation of PINK1 and Parkin to mitochondria, thereby activating mitophagy, reducing oxidative stress, and inhibiting inflammation. Interestingly, the renal protective effect of melatonin can be partially blocked by downregulation of PNK1 and inhibition of AMPK. Our studies demonstrated for the first time that melatonin plays a protective role in DN through the AMPK-PINK1-mitophagy pathway.